Epworth League at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the Epworth League California Convention at Monte Toyon. Several groups of attendees are holding signs or banners that read: "Hollister," "Los Gatos," "Roseville," "Salinas," "Watsonville," "Tracy," "Nevada Co.," "Crusaders," "Half Moon Bay," "Hayward"